2021
DOI: 10.1164/rccm.202006-2248oc
|View full text |Cite
|
Sign up to set email alerts
|

Mucus Plugs and Emphysema in the Pathophysiology of Airflow Obstruction and Hypoxemia in Smokers

Abstract: Rationale:The relative roles of mucus plugs and emphysema in mechanisms of airflow limitation and hypoxemia in smokers with chronic obstructive pulmonary disease (COPD) are uncertain.Objectives: To relate image-based measures of mucus plugs and emphysema to measures of airflow obstruction and oxygenation in patients with COPD.Methods: We analyzed computed tomographic (CT) lung images and lung function in participants in the Subpopulations and Intermediate Outcome Measures in COPD Study. Radiologists scored muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 20 publications
3
63
0
2
Order By: Relevance
“…[ 7 ] In our study, almost equal number of smokers and never smokers reported production of mucus or phlegm, which correlates with a well-known fact that smoke is a primary cause of goblet cell hyperplasia and resultant mucus hypersecretion in the pathophysiology of COPD. [ 8 ] This could explain the reason for increase mucus production reported by non-smoker COPD patients in our study as biomass fuel exposure is present in a majority of these patients. [ 9 ]…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[ 7 ] In our study, almost equal number of smokers and never smokers reported production of mucus or phlegm, which correlates with a well-known fact that smoke is a primary cause of goblet cell hyperplasia and resultant mucus hypersecretion in the pathophysiology of COPD. [ 8 ] This could explain the reason for increase mucus production reported by non-smoker COPD patients in our study as biomass fuel exposure is present in a majority of these patients. [ 9 ]…”
Section: Discussionmentioning
confidence: 80%
“…The chronic inflammatory process induced by tobacco smoking promotes thickening and narrowing of the small conducting airways, as well as destruction of the parenchyma and reduced alveolar-bronchiolar attachments. [ 8 11 12 ] More severe expiratory airflow obstruction in smokers could be secondary to these additional changes.…”
Section: Discussionmentioning
confidence: 99%
“…During an exacerbation event, mucin overproduction and its associated inflammation leads to airway obstruction, contributing to poorer lung function. Detecting and quantifying mucus plugs using multidetector CT in asthma and COPD is linked to airflow obstruction and poorer lung function outcomes [113,114]. Importantly, the prevalence of mucus hypersecretion is similar in patients with high and low mucus plug scores, highlighting the difficulties in using symptoms as a main surrogate for disease classification.…”
Section: Mucin In Chronic Pulmonary Diseasementioning
confidence: 99%
“…Radiologically, MP has been linked to severity of airflow obstruction, eosinophilic inflammation, and interleukin-4 blood levels in asthma [ 5 , 7 ]. In two smaller studies, MP was associated with worse lung function and health-related quality of life in smokers with and without COPD, but neither CB nor eosinophilia [ 3 , 8 ]. To date, this is the first study finding a significant association between mucus plugging and CB in a large cohort of COPD subjects.…”
Section: To the Editormentioning
confidence: 99%
“…More mucus plugs have been found in COPD subjects with worse airflow obstruction; additionally, more emphysema is seen in COPD patients with worse airflow obstruction. Previous smaller studies in smokers with and without COPD have found weak but significant correlations between mucus plugging scores and percent emphysema [ 3 , 8 ]. Our analysis was restricted to those with COPD, and we found statistically different amounts of percent emphysema between those with and without mucus plugs but the difference was not great.…”
Section: To the Editormentioning
confidence: 99%